Analisis Akting dalam Animasi Karakter Amatir dengan Tolok Ukur Profesional - Johanes Baptista Permadi (Bina Nusantara University, 2013)
Issue raised is the lacks of animation quality in facial expressions that often make the characters do not look quite alive. The method used to find a solution is recording human facial expressions as a reference in a state of silence, dialogue, movement, and interaction with the gadgets. Once the reference is obtained, the results of the study are implemented in a 3D model which is ready to be animated. The goal is to make animated facial expressions and lively as similar as possible to actual human facial expressions. After making the animation, the animation results are compared with the references recorded to infer the observation.